2016
DOI: 10.1002/malq.201400056
|View full text |Cite
|
Sign up to set email alerts
|

Dense codense predicates and the NTP2

Abstract: Abstract. We show that if T is any geometric theory having NTP 2 then the corresponding theories of lovely pairs of models of T and of H-structures associated to T also have NTP 2 . We also prove that if T is strong then the same two expansions of T are also strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…The following definition and proposition were very fruitfull to show the preservation of NTP2 to T ind when T was geometric; cf. . Definition Let false(M,Hfalse)TscriptG ind be saturated.…”
Section: Definable Sets In H‐structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The following definition and proposition were very fruitfull to show the preservation of NTP2 to T ind when T was geometric; cf. . Definition Let false(M,Hfalse)TscriptG ind be saturated.…”
Section: Definable Sets In H‐structuresmentioning
confidence: 99%
“…We also get by transitivity that a n+1 | Ca 1 ,...,a n H 1 The following definition and proposition were very fruitfull to show the preservation of NTP2 to T ind when T was geometric; cf. [3].…”
Section: P R O O Fmentioning
confidence: 99%
“…The approach we follow is to check the property by doing a formula-by-formula analysis, separating the cases when the corresponding definable set is small (algebraic over the predicate) or large. To show the preservation of NSOP 1 we build on ideas presented in [23], the proofs for the preservation of NTP 1 , NTP 2 generalize ideas presented in [2,18]. In Section 6, we study independence notions in the expansion, assuming the original theory has a good notion of independence.…”
Section: Introductionmentioning
confidence: 99%
“…The study of expansions in the NTP 2 context was undertaken in , where it was shown that the NTP 2 property is preserved under “dense and codense” unary predicate expansions of geometric structures where the unary predicate is assumed to define either an algebraically independent subset or an elementary substructure. In the present paper, we prove that the NTP 1 property is also preserved under such expansions.…”
Section: Introductionmentioning
confidence: 99%
“…Our paper is organized as follows. In § , we review some essential facts about dense codense predicate expansions from . In § , we state slightly modified versions of some results from concerning the SOP 2 , the strong order property of order 2 (equivalently, the TP 1 ).…”
Section: Introductionmentioning
confidence: 99%